Feeding Practice, Nutrition, and Growth in Infants with Abdominal Wall Defects and Esophageal Atresia: A Retrospective Case–Control Study - Sparre, Signe; Zachariassen, Gitte; Ellebæk, Mark Bremholm; Husby, Steffen; Holm, Kristina Garne (European Journal of Pediatric Surgery, 2022)
Introduction Infants born with abdominal wall defects and esophageal atresia (EA) are at risk of impaired growth. Little is known about the optimal nutritional strategy and its impact on growth for these infants. This study aims to explore nutrition, focusing on breastfeeding, and the presumed impact on infant growth during the first year of life.Materials and Methods We performed a registry study. The participants comprised infants born with gastroschisis, omphalocele, or EA from 2009 to 2020. Breastfed healthy infants from the Odense Child Cohort served as the control group. Descriptive statistics were applied when presenting data on nutrition. Growth data were converted to weight z-scores at birth and at discharge, and estimated weight z-scores at 6 and 12 months were calculated. Univariate regression analysis was applied.Results The study included 168 infants in the study group and 403 infants in the control group. Exclusive breastfeeding rates at discharge were as follows: 55.7% (gastroschisis), 58.3% (omphalocele), 50.9% (EA), and 7.7% (long-gap EA). For the study group our data demonstrate no difference in growth at 1 year of age when comparing mother's milk to formula feeding. During the first year of life, infants in the study group showed slower growth compared with the control group. At 12 months of age, all infants had a mean weight z-score above –2.Conclusion Breastfeeding in infants with abdominal wall defects and EA can be established without compromising growth. Mother's milk can be recommended for infants with abdominal wall defects and EA.
Keywords: congenital abdominal wall defect; esophageal atresia; breastfeeding; growth